Pulmonary Embolism Mimicking Pneumonia in a HIV Patient - Vivek Nagaraja; Joel A. Terriquez; Hemanth Gavini; Lokesh Jha; Stephen A. Klotz (Case Reports in Medicine)
Recent studies have shown an increased risk of arterial and venous vascular diseases in HIV patients, pulmonary thromboembolism being one of them. HIV-infected individuals may have procoagulants predisposing them to thromboembolism. Patients with thromboembolism may have a clinical presentation mimicking common opportunistic infections. It is important to consider pulmonary embolism in the differential of HIV patients with fever, cough, and dyspnea, particularly in those with well-controlled HIV infection.